PERANCANGAN SISTEM INFORMASI ARSIP DOKUMEN BERBASIS WEB PADA DINAS PERIKANAN BANYUWANGI - Kayyisah Fakhirah; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
Digitizing archives has become a crucial need in the technological era. Frequent problems with physical documents include lost and difficult-to-find documents, which can lead to difficulties in document management and information retrieval. The Banyuwangi Fisheries Service is a government agency responsible for managing and improving the fisheries sector. Currently, the document archiving data management process at the Fisheries Service is not yet integrated. The document archiving system at the Fisheries Service uses a manual system, which is handwritten and typed using Microsoft Excel. Therefore, a web-based document archiving information system is needed. This aims to develop and build a document management system, implementing a web-based archive management portal to facilitate employees, especially the archives department, so that the presentation is systematic, efficient, and useful. This information system is designed using Prototype and PHP programming, and its database uses MySQL